Adverse drug reactions associated with tyrosine kinase inhibitors in cancer patients: A retrospective cross-sectional study - Linh, Ton Nu Thi My; Dung, Nguyen Phuong; Tham, Pham Hong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Tyrosine kinase inhibitors (TKIs) demonstrate superior efficacy over conventional chemotherapy but are associated with various adverse drug reactions (ADRs) that can compromise therapeutic efficacy and patient adherence. Objectives: This study analyzed the ADRs associated with tyrosine kinase inhibitors (TKIs) prescribed for cancer patients undergoing treatment at the Oncology Department of Nhan Dan Gia Dinh Hospital. Methods: A retrospective cross-sectional study was conducted using outpatient records and TKI prescriptions collected from treatment encounters from June 2024 to June 2025. Results: Among the 449 TKI-containing prescriptions reviewed, 416 (92.7%) were associated with at least one ADR, while 33 prescriptions (7.3%) reported no ADRs. The most prevalent toxicities involved gastrointestinal (59.2%), skin and subcutaneous tissue disorders (58.6%), and hepatobiliary disorders (30.7%). Serious adverse events included interstitial lung disease (8.9%) and cardiac disorders (2.4%). Other observed ADRs were eye and general disorders (e.g., fatigue). Regarding concurrent toxicity (N = 416), 69.5% of cases involved 1-3 ADRs, while 23.2% experienced more than 3 ADRs. This high frequency of ADRs per TKI prescription reflects the complexity of the toxicity profile and the significant risk of patients facing concurrent adverse effects during targeted therapy. Conclusion: The use of TKIs in cancer patients is associated with a high prevalence of ADRs, primarily manifesting as gastrointestinal, skin, and subcutaneous tissue disorders, hepatobiliary disorders. These findings underscore the importance of careful monitoring and management of ADRs to optimize treatment efficacy. Furthermore, the frequent occurrence of concurrent ADRs necessitates a comprehensive pharmacovigilance approach. Early detection and proactive management of these toxicities are crucial to maintain treatment adherence and preserve the quality of life for cancer patients.